An insight into CO2 sequestration and EGR in Longmaxi and Niutitang shale formations via experimental analysis. (15th September 2022) - Finnian Ukaomah, Chima; Sun, Mengdi; Pan, Zhejun; Ostadhassan, Mehdi; Liu, Bo; Xu, Yanran; Istifanus Madaki, Agwom; Ijeoma Umeobi, Happiness; Dahiru Aminu, Mohammed; Yang, Baolin
Highlights: CO2 sequestration and EGR are experimentally evaluated in two shale gas reservoirs. Pore heterogeneity and connectivity are evaluated via multifractal analysis. Shale composition controls on gas storage is evaluated from gas adsorption measurements. Links between MICP and gas adsorption measurements were used to evaluate EGR suitability. Abstract: In the global effort toward climate change mitigation, geologic storage of CO2 in shale plays is becoming critical while it can improve production from these reservoirs. In this study, the gas storage capacity and CO2 sequestration suitability of the Longmaxi and Niutitang shale gas reservoirs is investigated and compared via XRD analysis, programmed pyrolysis, low pressure N2 and CO2 adsorption, high pressure CH4 adsorption, and MICP analysis. Results showed that clay and TOC controls on micropore heterogeneity and connectivity happens only within the Longmaxi Formation. Furthermore, both components play a role in the adsorbed quantities of gas in the formation which revealing a higher storage capacity in mesopore-macropores. This was verified by a positive correlation between adsorbed volume within the mesopore-macropore space. The Longmaxi Formation was also found to own better pore connectivity and PSD homogeneity of mesopore-macropores, indicating easier pathways for CO2 movement channels within the pore network. Furthermore, the samples from the Longmaxi exhibited a positive relationship between adsorbed volume with the CO2 breakthrough pressure and median pore diameter, alike between the mesopore-macropore volume and CO2 breakthrough pressure. This means, the injected CO2 will displace adsorbed methane within the mesopore-macropore and will be adsorbed and stored in such pores. Overall, superiority of the Longmaxi shale over the Niutitang for CO2 storage and EGR would be significant for future operations in similar shale gas reservoirs in China and around the globe.